Burden and outcome of acute copper sulphate poisoning in a teaching hospital - Mollick, SH; Mollick, KA; Bakar, A; Miah, María (Bangladesh Medical Journal Khulna, 2012)
Copper sulphate poisoning is the most common poisoning next to organophosphorus poisoning with significant mortality. Gastrointestinal, liver, renal and haematological toxicities are common. A prospective observational study was conducted in department of medicine, KMCH, Khulna during the period of September, 2005 to March, 2007 to observe the presentation and outcome of copper sulphate poisoning. Forty patients with acute copper sulphate poisoning of different age group of both sexes were studied. Patients were evaluated through detailed history, clinical features, laboratory investigations and they were monitored closely at regular interval during hospital stay. Copper sulphate poisoning was found mostly in rural people (85%) and maximum (62.5%) patient were in the young age group of 16-25 yr. All patients had taken it as a suicidal attempt. Almost all patients presented with gastrointestinal symptoms-nausea (100%), vomiting (100%) and abdominal pain (90%). Subsequently hepatic toxicity was manifested by jaundice (32%), yellowish discoloration of urine (35%) which developed usually on the 2nd or 3rd day. Renal toxicities were manifested by oliguria (25%), haematuria (32.5%), albuminuria (30%) and renal dysfunction (30%). 35% of the patients were found to have anemia with Hb below 60%. Eight patients (20%) became unconscious at the terminal stage and died. DOI: http://dx.doi.org/10.3329/bmjk.v44i1-2.10468 Bang Med J (Khulna) 2011: 44(1&2) 7-10